Pemberdayaan Masyarakat dalam Penanganan Pertolongan Pertama pada Kecelakaan (P3K) - Pannyiwi, Rahmat; Djunaedi, Djunaedi; Nurasbon, Nurasbon; Purwanto, Medy; Badaruddin, Badaruddin; Mahoklory, Serly Sani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Accidents can occur at any time and in any environment, so communities need basic skills in providing First Aid (P3K) to prevent the victim's condition from worsening. This Community Service (PKM) program aims to improve community knowledge, skills, and preparedness in handling emergencies through training, outreach, demonstrations, and field simulations. The program was conducted among residents of XX neighborhoods with 20 participants. Results showed a 20% increase in participants' understanding of First Aid principles and improved practical skills such as stopping bleeding, treating choking, splinting fractures, and Cardiopulmonary Resuscitation (CPR). This activity successfully created a more responsive, alert, and empowered community in dealing with emergency situations.